Ending Dirty Energy Policy : Prelude to Climate Change / [electronic resource] - Tomain, Joseph P. (Cambridge : Cambridge University Press, 2011)
Climate change presents the United States, and the world, with regulatory problems of a magnitude, complexity and scope unseen before. The United States, however, particularly after the mid-term elections of 2010, lacks the political will necessary to aggressively address climate change. Most current books focus on climate change. Ending Dirty Energy Policy argues that the US will not adequately address climate change until it transforms its fossil fuel energy policy. Yet there are signs that the country will support the transformation of its century-old energy policy from one that is dependent on fossil fuels to a low-carbon energy portfolio. A transformative energy policy that favors energy efficiency and renewable resources can occur only after the US has abandoned the traditional fossil fuel energy policy, has redesigned regulatory systems to open new markets and promoted competition among new energy providers, and has stimulated private-sector commercial and venture capital investment in energy innovations that can be brought to commercial scale and marketability.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Climatic changes; Renewable energy sources